Kampanye Global 16 Hari Anti Kekerasan terhadap Perempuan dalam Media Digital di Indonesia - Farahdiba Bachtiar; Alif Revka Mahesa (Program Studi Ilmu Komunikasi, FISIP Unismuh Makassar, 2026)
This article examines the mechanisms through which transnational actors, specifically Non-Governmental Organizations (NGOs) and Civil Society Organizations (CSOs), introduce gender cosmopolitan values into the 16 Days of Activism Against Gender-Based Violence (HAKTP) campaign in Indonesia. The analysis focuses on two primary dimensions: first, the impact of the internet on the escalation of Online Gender-Based Violence (OGBV) in Indonesia, and second, the contributions of digital platforms and social media utilized by NGOs and CSOs. To achieve this, the study integrates gender studies and communication theory to evaluate the extent of media roles in the localization of gender norms within the Indonesian context. Employing a qualitative research methodology, this study draws on secondary data from various authoritative sources. The findings indicate that digital media plays a significant role in the transnational gender movement in Indonesia, facilitated by the digital platforms of local and international NGOs and CSOs to disseminate the 16 HAKTP campaign. Simultaneously, the 16 HAKTP campaign distributed across various digital channels substantially reflects transnational activism that reconstructs pre-existing gender values and norms in Indonesia. The digitalization of norms through news and information—curated into diverse digital content and posts—ultimately bridges local and global narratives. This digital intervention aims to construct counter-narratives to mitigate the recent surge of OGBV in Indonesia.